2006
DOI: 10.1007/s00535-006-1852-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression in patients with severe acute pancreatitis

Abstract: Immunosuppression occurs from the early phase in SAP, and quantitative impairment of lymphocytes, mainly T lymphocytes, may be closely related to infectious complications during SAP. CD4- and CD8-positive lymphocyte counts on admission and the lymphocyte count on day 14 after admission may be useful for predicting infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 28 publications
6
46
0
Order By: Relevance
“…There is also evidence of an association with higher viral loads, suggesting that those with more advanced disease are at greater risk. Dragovic [3,9,18,19], the AP had occurred in our study in patients with acute immunosuppression with CD4 count less than 200 cells/mm 3 . Nadembèga affirms that the average rate of amylasemia is higher in patients with stage C than those in stage A and B (CDC classification).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…There is also evidence of an association with higher viral loads, suggesting that those with more advanced disease are at greater risk. Dragovic [3,9,18,19], the AP had occurred in our study in patients with acute immunosuppression with CD4 count less than 200 cells/mm 3 . Nadembèga affirms that the average rate of amylasemia is higher in patients with stage C than those in stage A and B (CDC classification).…”
Section: Discussionsupporting
confidence: 48%
“…Moore et al had reported a risk increase in patients receiving nucleoside reverse transcriptase inhibitors (NRTIs), especially didanosine [23]. Prolonged exposure to these molecules is associated with inhibition of DNA polymerase, the enzyme responsible for mitochondrial DNA replication, causing mitochondrial toxicity [4,18,24]. Under protease inhibitors especially in Lopinavir and Ritonavir, the AP is explained rather by the secondary hypertriglyceridemia, which is due to the decrease in peripheral clearance of triglycérides [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…However, apoptosis of CD4 lymphocytes was not related to the late resolution of SIRS. Lymphopenia arising in acute pancreatitis of either mild or moderate severity has also been described in other cohorts of patients [19,20]. …”
Section: Discussionmentioning
confidence: 98%
“…The risk of pancreatitis is increased for the HIV/AIDS patients with lower CD4 cell counts [36] . There is also evidence of an association with higher viral loads, suggesting that those with more advanced disease are at greater risk [17,21,35] .…”
Section: Cd4 Cell Count and Pancreatitismentioning
confidence: 99%